Gonadosomatic index and weight/length relationship in females of three penaeoidean shrimps impacted by fisheries on the southeastern Brazilian coast - Santos, Renan Augusto Pereira Dos [UNESP]; Silva, Alexandre Ribeiro Da; Moraes, Isabela Ribeiro Rocha De [UNESP]; Antunes, Mariana [UNESP]; Lopes, Ana Elisa Bielert [UNESP]; Costa, Rogério Caetano Da [UNESP]; Castilho, Antonio Leão [UNESP] (Sociedade Brasileira de Carcinologia, 2020)
The aim of this study was to evaluate the gonadosomatic index (GSI) and the weight/length ratio in important shrimp populations (Xiphopenaeus kroyeri (Heller, 1862), Litopenaeus schmitti (Burkenroad, 1936), Rimapenaeus constrictus (Stimpson, 1874)) from the northern littoral of São Paulo State. The samples were collected between 2015 and 2016, with 212 females that were identified, classified according to their gonadal development stage, and measured (CL). The gonads were macroscopically classified into immature, spent and developed, and were then removed. Both body (BodW) and gonad (GonW) dry weights were obtained in order to calculate the gonadosomatic index. Weight/length relationship and weight gain rate were assessed. The weight gain presented negative allometry, indicating that the animals grow faster than they gain weight. The weight/length relationship showed a pattern of continuous reproduction, as previously determined for tropical species. From the GSI values, it was possible to separate the three predetermined gonadal stages, proving that macroscopic evaluation is reliable for evaluating the reproductive period of these shrimps. These results can be used as a guide for fishery stocks management and monitoring.
Keywords: Allometry; gonads; reproduction; São Paulo State; Ubatuba